Designing a new aerodynamic profile for the SAE Brasil Aerodesign competition - Barbosa, Pedro Gabriel Nunes Magalhães; Ramirez, Bruna Niccoli; Costa, Anderson Figueiredo da (Seven Editora, 2023)
Aerodynamics is a science that is part of physics, and with the appearance of the first airplane it became more and more profound and a whole new area. His study influenced everything from the design of the Antonov An-225, which was the largest fixed-wing aircraft in the world before the War in Ukraine, to the design of model airplanes for the SAE Brasil Aerodesign competition. The work shows the study and design of a new aerodynamic profile for the USJT extension project, Equipe Ozires USJT Aerodesign. This new profile appears as an optimized alternative to two traditional profiles of the project, the E423 and S1223, offering superior properties mainly in its coefficient of support and performance. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-092